Tiger Becomes Termite Hill: Soliga/Solega Perceptions of Wildlife Interactions and Ecological Change - Agnihotri, Samira; Madegowda, C.; Si, Aung (Frontiers in Conservation Science, 2021)
The Solega community living in the Biligiri Rangan Hills (B. R. Hills) of Karnataka State, southern India, have noticed significant changes to the ecosystem of their forest homeland over the last four or five decades. Originally hunter-gatherers, who carried out swidden agriculture at a subsistence level, they were forced to abandon the semi-nomadic ways of their ancestors, and settle in permanent villages when these forests were first declared a wildlife sanctuary in 1974. In this paper, we present the views of Solega elders on the ecological changes that have taken place in the B. R. Hills, along with the subsequent changes in their interactions with the animals that also inhabit this landscape. The Solega way of life is accustomed to co-existing with wildlife, and they worship several animal deities. Their folklore and traditional ecological knowledge are also replete with ways of avoiding dangerous encounters with wildlife. Many of the detrimental ecological changes observed by Solega people are ascribed by them to the halting of their traditional litter fire regime, and the subsequent rampant growth of the exotic invasive plant Lantana camara, which now dominates the understorey in large swathes of the forest. These factors combine, according to Solega elders, to negatively impact the well-being of both animals as well as their own people. We hope to demonstrate how a deeper understanding of Solega language and culture, both essential facets of everyday life, as well as of their traditional ecological knowledge – can allow a full appreciation of the interactions between small Indigenous communities, such as the Solega, and the natural environment. We argue for a greater appreciation of, and engagement with, Indigenous knowledge in conservative efforts in countries such as India, where the protection of charismatic species, such as tigers, is often perceived to be at odds with the rights of small minority groups, such as the Solega.